Increasing Digital Literacy in Facing the 2024 Election in Patin Village - Kampar - Dian Rianita; Alexsander Yandra; Khuriyatul Husna (Universitas Lancang Kuning, 2023)
The advent of digital technology has had a tremendous influence on many aspects of people's lives, including politics. The election season is a crucial time for individuals to absorb news on social media, which can lead to discontent and conflict among constituents. To address this issue, a community service project consisting of participatory activities to enhance digital literacy in Kampung Patin is conducted. People will be more equipped to engage in critical thinking while reading and receiving news and recognize and avoid hoaxes and fake news as a result. This project aims to assist the community in becoming more critical and encourage active reduction of erroneous information that can potentially destroy national unity.